Quinacrine directly dissociates amyloid plaques in the brain of 5XFAD transgenic mouse model of Alzheimer’s disease - Sohui Park (Nature Portfolio, 2021)
Abstract Alzheimer’s disease (AD) is the most common type of dementia characterized by the abnormal accumulation of amyloid-β (Aβ) in the brain. Aβ misfolding is associated with neuroinflammation and synaptic dysfunction, leading to learning and memory deficits. Therefore, Aβ production and aggregation have been one of the most popular drug targets for AD. Failures of drug candidates regulating the aforementioned Aβ cascade stimulated development of immunotherapy agents for clearance of accumulated Aβ in the brain. Here, we report that quinacrine, a blood–brain barrier penetrating antimalarial chemical drug, dissociates Aβ plaques in the brain of AD transgenic mice. When co-incubated with pre-formed Aβ fibrils, quinacrine decreased thioflavin T-positive β-sheets in vitro, on top of its inhibitory function on the fibril formation. We confirmed that quinacrine induced dissociation of high-molecular-weight Aβ aggregates into low-molecular-weight species by dot blots in association with size cut-off filtrations. Quinacrine was then administered to adult 5XFAD transgenic mice via weekly intravenous injections for 6 weeks, and we found a significant reduction of Aβ plaques and astrocytosis in their cortex and hippocampus. In western blots of quinacrine-administered mouse brains, amelioration of AD-related biomarkers, glial fibrillary acidic protein, postsynaptic protein 95, phosphorylated cAMP response element-binding protein, phosphorylated c-Jun N-terminal kinase were observed. Lastly, quinacrine-stimulated dissociation of misfolded aggregates induced recovery of synaptic function associated with Aβ in excitatory post-synaptic current recordings of primary rat cortical neurons treated with Aβ aggregates and quinacrine. Collectively, quinacrine can directly dissociate Aβ fibrils and alleviate decreased synaptic functions.